2004
DOI: 10.1021/bi0497998
|View full text |Cite
|
Sign up to set email alerts
|

Novobiocin Induces a Distinct Conformation of Hsp90 and Alters Hsp90−Cochaperone−Client Interactions

Abstract: Hsp90 functions to facilitate the folding of newly synthesized and denatured proteins. Hsp90 function is modulated through its interactions with cochaperones and the binding and hydrolysis of ATP. Recently, novobiocin has been shown to bind to a second nucleotide binding site located within the C-terminal domain of Hsp90. In this report, we have examined the effect of novobiocin on Hsp90 function in reticulocyte lysate. Novobiocin specifically inhibited the maturation of the heme-regulated eIF2alpha kinase (HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
112
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(123 citation statements)
references
References 79 publications
10
112
0
1
Order By: Relevance
“…3B), NB also diminished direct interactions of Hsp90 with the preprotein. Our results extend earlier observations that NB can disrupt Hsp90 complexes with steroid receptors and kinases (59,60) by measuring a reduction in actual intermolecular contact.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…3B), NB also diminished direct interactions of Hsp90 with the preprotein. Our results extend earlier observations that NB can disrupt Hsp90 complexes with steroid receptors and kinases (59,60) by measuring a reduction in actual intermolecular contact.…”
Section: Resultssupporting
confidence: 90%
“…For a mechanistic comparison with NB, the effect of GA on import was also studied. Both drugs have been demonstrated to impair Hsp90 function, although much lower concentrations of GA are typically required: 0.5-10 M GA in live cells or 10 -100 M GA in vitro (48,(53)(54)(55)(56)(57)(58)(59)(60)(61). Such concentrations agree with the ϳ2 M affinity of GA for Hsp90 measured in vitro (53).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Novobiocin is a small molecule inhibitor that binds to the CTD of Hsp90 (Marcu et al, 2000a;Marcu et al, 2000b;Soti et al, 2002). Like GA and radicicol, novobiocin inhibits the formation of Hsp90 complexes with client or p23, but unlike GA it also reduces the affinity of Hsp90 for TPR-containing co-chaperones that bind to the CTD (Allan et al, 2006;Yun et al, 2004). The disruption of these Hsp90 complexes suggests that novobiocin causes structural rearrangements within Hsp90 that are distinct from the changes seen with GA. Epigallocatechin gallate (ECGG) the active ingredient found in green tea also directly binds to Hsp90 and acts as an AhR antagonist.…”
Section: Small Molecules Also Shift the Conformation Of Hsp90mentioning
confidence: 99%
“…The N-terminal nucleotide binding domain of Hsp90 is the site of action for the Hsp90 inhibitor geldanamycin (26 -28), whereas its C-terminal domain contains a binding site for novobiocin, which also inhibits Hsp90 function (29 -32). Analyses with these compounds, with nucleotides and nucleotide analogs, and with site direct mutants that alter Hsp90 ATP binding and/or ATPase activity have revealed that Hsp90 function is regulated via the binding and hydrolysis of ATP, which modulates the switching of Hsp90 between at least three alternative conformations (1)(2)(3)(4)32). In the presence of geldanamycin, Hsp90 binds weakly to client kinases in a salt-labile fashion (20,24,33).…”
mentioning
confidence: 99%